The Effectiveness of β-glucan in the Treatment of Caprine Mastitis Induced by Candida albicans - H Mahmoud, Saddam; N Yassein, Shaimaa (The Iraqi Journal of Veterinary Medicine, 2024)
This study evaluated the efficacy of β-glucan, extracted from Candida albicans isolated from mastitic goat milk using an alkaline-acidic method, in treating C. albicans-induced mastitis. Twenty lactating goats (2–4 years old, 25–30 kg) were randomly divided into five groups (Group I–Group V), with each group consisting of four goats. Sixteen goats were intramammarily inoculated with 1.2 × 10⁷ yeast/2 mL of virulent C. albicans. The groups were as follows: Group I (negative control, uninfected), Group II (positive control, infected but untreated), Group III (treated with Nystatin, 200,000 units/half udder/day intramammary for 7 days), Group IV (treated with β-glucan, 5 mg/mL/half udder, administered intramammary every 48 h for three doses), and Group V (treated with a combination of β-glucan and Nystatin; β-glucan was administered as in Group IV, followed 2 h later by Nystatin, 200,000 units/half udder/day for 7 days). Clinical signs, milk quality (California Mastitis Test and fungal cultures), and serum levels of IL-6 and IFN-γ were assessed on days 0, 5, 10, 20, 30, and 40 post-inoculation. The results showed that the positive control group exhibited persistent mastitis symptoms throughout the study. Goats treated with β-glucan alone (Group IV) demonstrated significant symptom reduction and fungal elimination by day 15. The combination therapy group (Group V) achieved similar improvements by day 25. Serum IL-6 and IFN-γ levels were significantly elevated in the positive control group, while the β-glucan-treated group showed a substantial reduction in these inflammatory markers, indicating its potential as a standalone antifungal therapy. The Nystatin group (Group III) and the combination group (Group V) also exhibited reduced cytokine levels, although these were higher than those observed in the β-glucan and negative control groups. This study confirms the potential of β-glucan as an effective treatment for C. albicans-induced mastitis in goats. Its ability to lower inflammatory cytokine levels and eliminate fungal infections highlights its promise as a therapeutic option, particularly in combination with Nystatin, for managing fungal mastitis‎‎‎.